Threats to Our Ocean Heritage: Bottom Trawling
XVII, 109 p. 29 illus., 27 illus. in color.
Keywords: This open access book focuses on the destruction of our Ocean Heritage from bottom trawling. It brings together the natural and cultural sides of the marine environment to further our understanding of the importance of this heritage, how it is threatened by activities such as bottom trawling, and provides recommendations, such as a moratorium in particularly vulnerable areas that are currently unprotected. It is a unique publication in integrating cultural heritage into a discussion where the primary focus has been the destruction of natural heritage The book is divided into three sections that discuss, respectively, the international legal context, history and ecological impact of bottom trawling, case studies highlighting the impact of these destructive activities on underwater cultural heritage, and finally recommended future steps and how to use the damage presented here to halt future devastation. This book is a valuable tool for resource managers and representatives of governments and international organizations in their efforts to establish the moratoria called for. This book is also of interest to educators, archaeologists and practitioners working in the field of underwater cultural heritage. This is an open access book.